Co-postseismic hydrogeochemical anomalies in a volcanic environment - P. F. Biagi; O. Molchanov; R. Piccolo; A. Minafra; A. Ermini; V. Capozzi; Y. M. Khatkevich; E. I. Gordeev (Copernicus Publications, 2003)
For many years flow-rate, temperature, ions and gases content data have been collected from a natural spring located in the Koryakskiy volcano area (Kamchatka, Russia). We have investigated the correlations between the hydrogeochemical data and the areal seismicity represented by the k s values ( k s is a function of magnitude and hypocentral distance) of the earthquakes. At first we smoothed the raw hydrogeochemical data using a semi-triangle weight function. Then we compared the trends of each smoothed hydrogeochemical parameter with the k s trend using a running cross-correlation function with a maximum lag of ± 30 days and the main result was that, sometimes, we found 0.7–0.4 cross-correlation coefficients with no lag for flow rate and with + (10 – 15) days lags for some ion and gas contents. The correlation is positive, i.e. flow rate and ion and gas contents increase when k s increases. This phenomenology could be explained by an underground water pumping produced by some earthquake. We advance the hypothesis that this pumping could be the response of the viscoelastic underground medium of the Koryakskiy volcano to seismic waves. So, sometimes, the supply of elastic energy of the earthquakes may provide the trigger to a catastrophic nucleation of bubbles of this material producing a new melt with a lower density which will tend to expand and cause a pressure increase. This pressure produces a more intensive circulation of underground water and an anomalous increase of the flow rate and subsequently anomalous increases in groundwater ions and gases content.